Atezolizumab plus carboplatin and nab‐paclitaxel versus carboplatin and nab‐paclitaxel as treatments for Chinese, treatment‐naïve, stage IV, non‐squamous, non‐small‐cell lung cancer patients: A retrospective analysis - Yingkai Chen; Shizhou Kang; Ming Yan (Wiley, 2022)
Abstract The IMpower trials reported significant effects of atezolizumab‐containing chemotherapies on Caucasian patients. Chinese patients differ from their Western counterparts in terms of driver mutations, etiologies, and regimen tolerance. In China, atezolizumab‐containing chemotherapies are not cost‐effective. Atezolizumab addition triggers grade >3 adverse events. Here, we evaluated the effectiveness and the safety profile of atezolizumab plus carboplatin and nab‐paclitaxel compared to carboplatin and nab‐paclitaxel in treatment‐naïve Chinese patients with confirmed stage IV, non‐squamous, non‐small‐cell lung cancer. All patients completed six cycles of 1200 mg of atezolizumab/3 weeks plus 6 mg/ml/min area‐under‐the‐curve carboplatin/3 weeks plus 100 mg/m2 nab‐paclitaxel/week (n = 115; ACN cohort) or 6 mg/ml/min area‐under‐the‐curve carboplatin/3 weeks plus 100 mg/m2 nab‐paclitaxel/week (n = 130; CNP cohort). The progression‐free survival (12.98 ± 2.57 months vs. 10.89 ± 2.18 months, p < .0001) and overall survival (38.04 ± 19.8 months vs. 33.59 ± 87 months, p = .012) of patients in the ACN cohort were higher than those of patients in the CNP cohort after 48 weeks of follow‐up. A total of 97 (84%) patients in the ACN cohort and 94 (72%) in the CNP cohort developed grade ≥3 adverse events (p = .030). A total of 84 (73%) patients from the ACN cohort and 107 (82%) from the CNP cohort died during 48 weeks of follow‐up (p = .091). The addition of atezolizumab to carboplatin and nab‐paclitaxel enhanced progression‐free and overall survival but increased the risk of grade ≥3 adverse events in Chinese, treatment‐naïve, stage IV, non‐squamous, non‐small‐cell lung cancer patients who completed treatment (Level of Evidence: III; Technical Efficacy Stage: 4).